조경식재공사 설계변경 유형 및 변경 적합성에 대한 인식 분석 -A공사 아파트단지 식재공사를 중심으로 - 박재영; Jae Young Park; 조세환; Se Hwan Cho (한국조경학회지, 2014)
본 연구는 ‘A’공사에서 발주된 아파트 단지 조경식재공사에서 발생하는 설계변경의 유형과 설계변경의 적합성 인식을 분석함으로써 향후 조경식재공사의 설계변경을 효율적으로 관리하기 위한 기초 자료 제시를 목적으로 수행하였는바 다음과 같은 결론이 도출되었다. 첫째, 2기 신도시 건설 이후 ‘A’공사에서 발주하여 시행된 수도권 현장 자료를 중심으로 조사·분석을 실시하여 ‘이미지 개선을 위한 설계변경’, ‘설계내역의 불일치로 인한 설계변경’, ‘현장조사 미비로 인한 설계변경’, ‘이용자 미고려로 인한 설계변경’, ‘시공성의 고려로 인한 설계변경’, ‘유지관리의 용이함을 위한 설계변경’, ‘타 공종과의 관계로 인한 설계변경’ 등 총 7가지의 조경식재공사 설계변경 유형을 구분할 수 있었다. 둘째, 17개 주거단지에서 총 553건의 조경공사 설계변경이 있었고, 그 중 조경식재공사 설계변경은 37.6%에 해당하는 208건이 나타났다. 또한, 식재 설계변경으로 인하여 생기는 공사비의 유동성으로 인해 당초 계획된 공사비의 변경으로 부정적인 영향을 낳는 것으로 파악되었다. 셋째, 조경식재공사 설계변경은 ‘이미지 개선에 의한 설계변경’과 ‘설계내역 불일치에 의한 설계변경’이 조경식재공사 설계변경에서 절대적인 부분을 차지하고 있는 것으로 나타났다. 넷째, 조경분야 전문가를 대상으로 타당성 검증을 실시한 결과, 본 연구에서 도출한 7가지의 조경식재공사 설계변경 유형의 통계값이 모두 유의한 것으로 나타났다. This study was conducted to analyze the recognition of the validity of the design changes that classified the type of design changes that occurred in the Apartment Complex Landscaping Planting Construction that have been ordered in ‘A`` work. This research was also carried out for the purpose of presentation of the basic data in order to effectively manage the change order of landscape-planting construction`s future work. The following conclusions were derived. First, the 7 types of change orders in planting design were delineated as ‘design changes for image improvement’, ‘design changes due to the mismatch of design statement’, ‘design changes due to lack of field study’, ‘design changes for consideration of the user’, ‘design changes due to consideration of the workability’, ‘the design changes for ease of maintenance’, and the ‘design changes due to the relationship with the Engineering species of other.’ Second, it is possible to produce a negative impact of all construction costs have increased due to design changes of landscaping planting construction is grasped. Third, There were the most frequent change order in planting design for the ‘image improving’, ‘due to the mismatch of planting design to the site situation.’ Fourth, the results of confirmatory targeting professional landscaping areas, was found that the statistics of the type of change landscaping planting construction design seven derived in this study is valid.